Community Empowerment: Exploring Food Safety and Halal Standards Through International Law Approach - Sitamala, Afandi; Johan, Eva; Vitrana, Mokhamad Gisa; Anom, Surya; Danial, Danial; Putra, Hilton Tarnama; Susanti, Hera; Hany, Elbirra Malida; Rosita, Ita; Oktrian, Pryanka Ceza; Kania, Sekar Puteri (Probono and Community Service Journal, 2024)
This study addresses the critical need for increased understanding of halal product certification among Micro and Small Enterprises (MSEs) in Pasanggrahan Village, Indonesia. Halal compliance, encompassing raw materials, production processes, and storage, is essential but difficult for consumers to verify without certification. The Indonesian government, through Law No. 33 of 2014, aims to ensure halal product availability, safety, and value for businesses. This research focuses on empowering local communities by combining halal education and legal counseling to enhance MSEs' understanding of halal certification. The findings highlight the importance of joint supervision and collaboration with village officials to ensure compliance and support local enterprises. This study contributes to improving halal certification awareness and strengthens the legal framework for halal product assurance in Indonesia.